Endothelial Progenitor Cells: A Vascular Perspective for Inflammatory Rheumatic Disorders - Avouac, Jerome; Uzan, Georges; Juin, Fabrice; Kahan, Andre; Boileau, Catherine; Allanore, Yannick (Current Rheumatology Reviews, 2007)
In human adults, new blood vessels may form in two ways: via endothelial sprouting from pre-existing endothelial cells/angioblasts (angiogenesis) or via the peripheral recruitment of endothelial progenitor cells (EPCs) (vasculogenesis). EPCs, which have been recently discovered, are a population of bone marrow-derived cells capable of differentiating into mature endothelial cells, and participating in the formation of new blood vessels. The molecular phenotype of EPCs and processes leading to their mobilization from bone marrow and homing to neovascularization sites remain unclear. There is still debate regarding methods for their quantification and isolation. Evidence is growing for vascular involvement in inflammatory rheumatic diseases. Recent studies suggest that EPCs in rheumatoid arthritis are involved in synovial vascularization, and may contribute to the increased cardiovascular morbidity and mortality, known features of this disease. Data available in systemic sclerosis is consistent with the hypothesis that EPCs are recruited during active disease; however, their levels may be depleted as the disease progresses and under chronic ischemic conditions. Other inflammatory disorders have not yet been investigated. EPCs are important in vasculogenesis, and may be involved in other features of inflammatory rheumatic disorders. There are various interesting pathophysiological aspects to these cells, for example as pathogenic actors and/or biomarkers, and which may have therapeutic significance.
Keywords: endothelial progenitor cells